Administrative conditions in Kirkuk (1921-1958) (Journal of the College of Basic Education, 2022)
Kirkuk is a city dating back to ancient times. It was a religious center in the Assyrian era, and in the Islamic eras (Umayyad and Abbasid) it became affiliated to Daquq. However, the city regained its importance in the ninth century AH, the fifteenth century AD, and there was the first reference to calling it “Kirkuk” instead of “Kirkuk”. Karkhini" in the ninth century AH, the fifteenth century AD.Despite the administrative importance of Kirkuk and its impact on the modern and contemporary history of Iraq, it has not received sufficient attention from researchers in terms of being the reservoir of Iraq's oil wealth, its fertile soil, and the crossroads connecting northern Iraq with its middle and south.